OcclusionChip: A functional microcapillary occlusion assay complementary to ektacytometry for detection of small-fraction red blood cells with abnormal deformability - Man, Yuncheng; An, Ran; Monchamp, Karamoja; Sekyonda, Zoe; Kucukal, Erdem; Federici, Chiara; Wulftange, William J.; Goreke, Utku; Bode, Allison; Sheehan, Vivien A.; Gurkan, Umut A. (Frontiers in Physiology, 2022)
Red blood cell (RBC) deformability is a valuable hemorheological biomarker that can be used to assess the clinical status and response to therapy of individuals with sickle cell disease (SCD). RBC deformability has been measured by ektacytometry for decades, which uses shear or osmolar stress. However, ektacytometry is a population based measurement that does not detect small-fractions of abnormal RBCs. A single cell-based, functional RBC deformability assay would complement ektacytometry and provide additional information. Here, we tested the relative merits of the OcclusionChip, which measures RBC deformability by microcapillary occlusion, and ektacytometry. We tested samples containing glutaraldehyde-stiffened RBCs for up to 1% volume fraction; ektacytometry detected no significant change in Elongation Index (EI), while the OcclusionChip showed significant differences in Occlusion Index (OI). OcclusionChip detected a significant increase in OI in RBCs from an individual with sickle cell trait (SCT) and from a subject with SCD who received allogeneic hematopoietic stem cell transplant (HSCT), as the sample was taken from normoxic (pO2:159 mmHg) to physiologic hypoxic (pO2:45 mmHg) conditions. Oxygen gradient ektacytometry detected no difference in EI for SCT or HSCT. These results suggest that the single cell-based OcclusionChip enables detection of sickle hemoglobin (HbS)-related RBC abnormalities in SCT and SCD, particularly when the HbS level is low. We conclude that the OcclusionChip is complementary to the population based ektacytometry assays, and providing additional sensitivity and capacity to detect modest abnormalities in red cell function or small populations of abnormal red cells.